Międzynarodowe zespoły zarządzające na przykładzie firmy Bosch - Malon-Schulze, Sylwia (International teams management on the basis of Bosch company, 2006)
The paper is an attempt to recognize German and Hungarian culture characteristic and differences between them. An organization is created by people that have their own goals, purposes and values. It includes not only people from different groups or so-called functioning cells, but people of different nationalities and different personalities. How to put together pieces that do not fit? How, in spite of different views and hierarchies of values, respect each other?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 70-76